ศึกษาวิเคราะห์ประโยชน์ทางจริยธรรมของความเชื่อเรื่องเทวดาในพุทธปรัชญาเถรวาท - พุทฺธวีโร (เกลี้ยงพร้อม), พระมหาสมพร (วารสาร ศึกษาศาสตร์ มมร, 2019)
การวิจัยนี้ มีวัตถุประสงค์ ๓ ประการ คือ (๑) เพื่อศึกษาแนวคิดความเชื่อเรื่องเทวดาในทางพุทธปรัชญาเถรวาท (๒) เพื่อศึกษาแนวคิดเรื่องประโยชน์ทางจริยธรรมในทางพุทธปรัชญาเถร-วาท (๓) เพื่อวิเคราะห์แนวคิดเรื่องประโยชน์ทางจริยธรรมของความเชื่อเรื่องเทวดาในทางพุทธ-ปรัชญาเถรวาท การวิจัยนี้เป็นการศึกษาเชิงคุณภาพ ผลการวิจัยพบว่า ๑). เทวดาเป็นเพื่อนร่วมเกิด แก่ เจ็บตาย เวียนว่ายอยู่ในวัฏฏสงสาร เพราะเคยสร้างความดีไว้ เช่น ให้ทาน รักษาศีล เจริญภาวนา มีความละอายความชั่วกลัวบาป บำเพ็ญวัตตบท ๗ สัมปทา ๔ เจริญเทวตานุสสติ เมื่อตายจึงไปสุคติโลกสวรรค์ ๒). ประโยชน์ทางจริยธรรมในทางพุทธปรัชญาเถรวาท มี ๓ ประการ คือ ๑.ประโยชน์ในโลกนี้ ก่อให้เกิดประโยชน์สุขในปัจจุบัน ๒.ประโยชน์ในโลกหน้า ทำให้เกิดเป็นมนุษย์ เทวดา หรือพรหมชั้นต่าง ๆ ๓.ประโยชน์อย่างยิ่ง ได้แก่ การบรรลุ มรรค ผล และนิพพาน ๓). แนวคิดเรื่องประโยชน์ทางจริยธรรมของความเชื่อเรื่องเทวดาในพุทธปรัชญาเถรวาท มี ๓ ประการ คือ ๑. ประโยชน์ในโลกนี้ ได้แก่ ๑.๑ ประโยชน์ต่อตนเอง คนที่ประพฤติเทวธรรม ย่อมไม่ทำชั่วทางกาย ทางวาจา ทางใจ จึงไม่ประสบความทุกข์ ไม่มีความเดือดร้อนจากกรรมชั่ว ประสบแต่ความสุข ความสงบเท่านั้น ๑.๒ ประโยชน์ต่อส่วนรวม เกิดประเพณีอันดีงาม เช่น ประเพณีบวชต้นไม้ในป่า รักษาต้นไม้ไม่ให้ถูกตัด เพราะกลัวรุกขเทวดาจะลงโทษ ทำให้มีป่าไม้อุดมสมบูรณ์ ประเพณีลอยกระทง เพื่อขอขมาแม่คงคา สร้างจิตสำนึกในการอนุรักษ์ ใช้น้ำอย่างประหยัด ไม่ทิ้งขยะลงแม่น้ำ เป็นต้น ๒.ประโยชน์ในโลกหน้า ผู้มีเทวธรรมประจำใจ มีความละอายชั่วเกรงกลัวต่อบาป ประพฤติสุจริตธรรม เมื่อคราวละจากโลกนี้แล้ว เมื่อไปสู่โลกหน้า ย่อมจากไปโดยอาการอันสงบ ได้บังเกิดในมนุษย์หรือในสวรรค์ ๓. ประโยชน์อย่างยิ่ง การบรรลุธรรมต้องลงมือปฏิบัติด้วยตนเองเท่านั้น แต่บางคนมีศักยภาพจำกัด ต้องอาศัยกัลยาณมิตร แนะประโยชน์ เทวธรรม ช่วยยกจริยธรรมให้สูงขึ้น เป็นบาทฐานในการยกจิตจากโลกิยะเป็นโลกุตระ คือ มรรค ผล และนิพพาน ต่อไป This thesis has 3 objectives : (1) to study the belief in gods in Theravada Buddhist philosophy, (2) to study the concept of ethical benefits according to Theravada Buddhist philosophy, and (3) to analyze the concept of ethical benefits of belief in gods in Theravada Buddhist philosophy. This research is a qualitative study. The conclusion of research findings are as follows: A god according to Theravada Buddhist philosophy is a being which is subject to birth, old age, sickness, and death like other beings in the universe. They have done good deeds such as making offerings (Dāna), keeping precepts (Sīla), practicing meditation (Bhāvanā), have moral shame, and fear of wrongdoing, practice seven principles of conduct, four accomplishment of persistent effort (Sampadā), practice recollection of deities (Devatānusati) regularly, and when they die they go to heavenly realms and take pleasure in the heavenly realms having celestial age, celestial skin, and celestial happiness until the end of life. The three kinds of ethical benefits in Theravada Buddhist philosophy are: 1. Benefits in this life; present happiness. 2. Benefits in the next life; to be born as a human being, deities (Devas) or Brahmās of different realms, 3. The greatest benefits which are attaining the path and fruit of Niḅbana. The belief in gods in Theravada Buddhist philosophy have 3 kinds of benefits: 1. Benefits in this life: 1.1 self-benefit, the one who practices Dharma of deities, having Hiri-Ottappa (moral shame and fear of wrongdoing), three kinds of meritorious action, seven principles of conduct, and recollection of deities (Devatānusati) regularly, would not do evil physically, verbally and mentally. Thus, they have no sufferings, no trouble from evil kamma, experiences only happiness and peacefulness. 1.2 Public benefits having good tradition such as; tree ordination ceremony in the forest to maintain it and keep them from being cut due to the fear of being punished by the Tree-spirit (Rukkhadevatā), making them the abundant forest. Loy Krathong festival, to apologize the Mother River, building awareness in conserving the river, using water sufficiently, not throwing the garbage into the river etc. 2. Benefits in next life; one with the dharma of deities (Devadhaṃma) has shame and fear of wrongdoing, conduct honesty, when they leave this world to next world they leave peacefully. Born at the heavenly realms as the Buddha’s word “Ciṭte Asankilitthe Sugati Patikankha” which means when the mind is undefiled, a happy destination can be expected. 3. The greatest benefits are the path and the fruit of Niḅbana. The attainment must be practiced only by oneself, but some have limited potential who must rely on spiritual friend to benefit and point out the way to help raise the ethical level higher as the base of upgrading from mundane to supramundane dharma as the path and fruit of Niḅbana further. Keywords : being, ethical, precepts, meditation, dharma of deities.